2017
DOI: 10.1289/ehp1239
|View full text |Cite
|
Sign up to set email alerts
|

Major Limitations in Using Element Concentrations in Hair as Biomarkers of Exposure to Toxic and Essential Trace Elements in Children

Abstract: Background:Hair is a commonly used exposure biomarker for metals and other trace elements, but concern has been raised regarding its appropriateness for assessing the internal dose.Objectives:The aim of the present study was to evaluate children’s hair as biomarker of internal dose for toxic (As, Mn, Cd, Pb) and essential elements (Mg, Ca, Fe, Co, Cu, Zn, Se, Mo).Methods:In 207 children (9–10 years of age), originating from a population-based cohort in rural Bangladesh, we measured concentrations of the select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 46 publications
7
30
1
Order By: Relevance
“…We recently reported that selenium concentrations in hair correlated positively with concentrations in erythrocytes (Spearman’s rank correlation coefficient of 0.54 for samples representing the time of blood collection) in children from the same study population ( Skröder et al 2017 ). Therefore, we also used hair selenium concentrations to assess selenium status at the 10-y follow-up.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…We recently reported that selenium concentrations in hair correlated positively with concentrations in erythrocytes (Spearman’s rank correlation coefficient of 0.54 for samples representing the time of blood collection) in children from the same study population ( Skröder et al 2017 ). Therefore, we also used hair selenium concentrations to assess selenium status at the 10-y follow-up.…”
Section: Methodsmentioning
confidence: 96%
“…Hair samples were cut from the occipital part of the children’s heads using 18/8 stainless steel scissors and were transported in high-quality paper envelopes to Karolinska Institutet (Stockholm, Sweden) for analyses ( Skröder et al 2017 ). A sample of of hair (closest to the scalp) was washed in 2% Triton X-100 solution for 1 h, rinsed 10 times with deionized water, and dried for 24 h at room temperature ( ).…”
Section: Methodsmentioning
confidence: 99%
“…The relevance of hair manganese concentrations is not completely clear. In general, manganese levels in hair do not correlate with manganese blood concentrations . This may be due to the fact that hair levels likely reflect a cumulative exposure over a longer period of time, whereas blood levels might strongly depend on sampling time as they rather reflect recent exposure.…”
Section: Manganese In the Human Bodymentioning
confidence: 92%
“…This may be due to the fact that hair levels likely reflect a cumulative exposure over a longer period of time, whereas blood levels might strongly depend on sampling time as they rather reflect recent exposure. It was further suggested that hair manganese levels might be influenced by hair color, and hair distance from skull . Even more important, hair manganese levels are prone to external contamination with manganese containing dust or water.…”
Section: Manganese In the Human Bodymentioning
confidence: 99%
“…Regarding this last point, chemical speciation could be enlarged from As and Hg to other elements [33][34][35]. Finally, Skröder [36] proposed to limit the relevance of children's hair as exposure biomarkers to only As and Se among 12 elements studied. These elements were apparently not affected by external contamination after washing the samples using Triton X.…”
Section: Tnmentioning
confidence: 99%